2000
DOI: 10.1111/j.1365-2141.2000.02407.x
|View full text |Cite
|
Sign up to set email alerts
|

Parvovirus B19 transmitted by bone marrow

Abstract: Summary. We describe a case of symptomatic parvovirus B19 infection transmitted by bone marrow (BM). The infection caused prolonged anaemia, thrombocytopenia, arthralgia and erythema infectiosum in a 16-year-old girl with acute myeloid leukaemia receiving a BM transplant (BMT). The BM donor was a 19-year-old asymptomatic brother who had parvovirus B19 viraemia at the time of BM harvest. Sequencing of the VP2 gene from the patient and the donor showed a perfect match of DNA sequences, confirming the mode of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Parvovirus B19 is most often transmitted by respiratory tract secretions, but transmission by the transfusion of RBCs, 19 PLTs, 20 clotting factor concentrates, 2122 and IVIG 23 has been well documented. In addition, transmission of parvovirus by allogeneic marrow progenitor cells has been previously confirmed 12 . Our case illustrates that the PBPCs are a potential source of parvovirus infection after autologous BMT.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Parvovirus B19 is most often transmitted by respiratory tract secretions, but transmission by the transfusion of RBCs, 19 PLTs, 20 clotting factor concentrates, 2122 and IVIG 23 has been well documented. In addition, transmission of parvovirus by allogeneic marrow progenitor cells has been previously confirmed 12 . Our case illustrates that the PBPCs are a potential source of parvovirus infection after autologous BMT.…”
Section: Discussionsupporting
confidence: 72%
“…Parvovirus infection has been shown to cause PRCA, chronic anemia, and engraftment failure after allogeneic BMT 5,6 , 12‐16 and PRCA after autologous BMT 17 . In many cases, the source of infection is difficult to ascertain.…”
Section: Discussionmentioning
confidence: 99%
“…However, nucleic acid testing (NAT) is available for plasma units in process of being fractionated . There is evidence that transmission of parvovirus B19 infection may occur at the time of transplantation . Barzon et al showed that in the majority of 10 pediatric kidney transplant patients (pretransplant parvovirus serology D+/R−), positive detection of parvovirus B19 DNA in the allograft kidney biopsy sample, preservation solution or washing solution (which contain circulating donor cells and resident kidney cells) was associated with posttransplant detection of parvovirus DNA in the blood of the recipient .…”
Section: Epidemiologymentioning
confidence: 99%
“…During parvovirus B19 infection, viremia usually persists for about a week, but virus DNA may be detectable by PCR methods for extended periods of time in serum (8, 12–14) and bone marrow (15), even in healthy, non‐anemic, asymptomatic individuals. Epidemiologic studies revealed that DNA B19 positivity among blood donors can be found with varying, usually very low frequency (according to various studies, from 0.003% to 0.6%) and there are reports in the literature that B19 may be transmitted by bone marrow (2, 8, 16) and blood‐derived products such as platelets (17) or intravenous immunoglobulin (18). Parvovirus B19 infection has also been reported in patients receiving solvent‐ or detergent‐treated plasma (19, 20).…”
Section: Discussionmentioning
confidence: 99%
“…Transmission of parvovirus B19 infection poses a risk of persistent infection and chronic anemia for immunocompromised patients, solid organ transplantation and bone marrow recipients, as well as for HIV patients. There are proposals that B19 screening of blood components destined for children with malignancies (20) and testing of bone marrow donors before transplantation should be considered (16). Because the overall rate of infection is low, testing all donors may be unnecessary, but this precaution especially applies to child recipients, as at a younger age there is greater possibility that the recipient may be seronegative, and also applies to patients receiving blood components derived from multiple blood units (such as clotting factors concentrates).…”
Section: Discussionmentioning
confidence: 99%